Impact of fatigue on health-related quality of life and illness perception in a monocentric cohort of patients with systemic lupus erythematosus. Issue 1 (18th February 2020) - Elefante, Elena; Tani, Chiara; Stagnaro, Chiara; Ferro, Francesco; Parma, Alice; Carli, Linda; Signorini, Viola; Zucchi, Dina; Peta, Umberto; Santoni, Adele; Raffaelli, Leonardo; Mosca, Marta
Abstract : Background: Fatigue is a very common and debilitating symptom in patients with systemic lupus erythematosus (SLE), even among those with a mild or inactive disease. The objective of this study is to define fatigue determinants and describe the impact of fatigue on health-related quality of life (HRQoL) and illness perception in a monocentric cohort of patients with SLE. Methods: This is a cross-sectional study. Adult patients with SLE were included. For each patient, demographics, medications, comorbidities, organ damage (Systemic Lupus International Collaborating Clinics Damage Index), active disease manifestations and Systemic Lupus Disease Activity Index scores were collected. It was evaluated if each patient met the definitions of remission and low disease activity. At enrolment, each patient completed the Short Form-36 (SF-36), Functional Assessment Chronic Illness Therapy-Fatigue (FACIT-F), Lupus Impact Tracker (LIT), Systemic Lupus Activity Questionnaire (SLAQ) and Brief Index of Lupus Damage (BILD). The FACIT-F questionnaire was also administered to a group of healthy controls. Results: 223 patients were included (mean age 44.9±13.2 years, median disease duration 13 years). 18.2% had an active disease, 43.5% met the definition of remission on treatment, and 11.8% had a concomitant fibromyalgia. The median FACIT-F score of our cohort was significantly lower compared with that of healthy controls (40 vs 47; p<0.001). FACIT-F scores were irrespective of age, disease duration, disease activity and damage. FACIT-F score was significantly lower in patients with fibromyalgia (p<0.01). FACIT-F scores demonstrated a significant correlation with all other patient-reported outcomes: SF-36 (r=0.53–0.77), LIT (r=−0.78), SLAQ (r=−0.72) and BILD (r=−0.28). Conclusions: Fatigue in patients with SLE has a strong negative impact on HRQoL and patient perception of the disease burden. Fatigue seems irrespective of disease activity but significantly influenced by the presence of fibromyalgia.